2004
DOI: 10.1002/path.1587
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiological implications of the expression of markers of testicular carcinoma in situ by fetal germ cells

Abstract: Several proteins, such as the placental/germ cell alkaline phosphatases (PLAPs), the stem cell factor receptor c-KIT, and the transcriptional regulator and marker of pluripotency OCT3/4, have been found in both normal immature and malignant germ cells, known as carcinoma in situ/intratubular germ cell neoplasia unclassified (CIS/ITGCNU). In the present study, immunohistochemical methods were used to evaluate the expression of these markers in a series of male gonads from fetuses from the second and third trime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
209
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(226 citation statements)
references
References 43 publications
11
209
1
5
Order By: Relevance
“…Indeed, the gene expression profile of GCNIS and fetal germ cells differed for only 5 genes in one gene expression study (Sonne et al, 2009). In particular, PLAP, KIT, OCT3/4 and Ki-67 are expressed in GCNIS, lending support to the hypothesis that it arises from a fetal gonocyte (Honecker et al, 2004). Further, the low level of DNA methylation in GCNIS is thought to reflect the stage at which the germ cell became developmentally blocked i.e.…”
Section: Defective Germ Cell Development Seeds Gcnissupporting
confidence: 54%
“…Indeed, the gene expression profile of GCNIS and fetal germ cells differed for only 5 genes in one gene expression study (Sonne et al, 2009). In particular, PLAP, KIT, OCT3/4 and Ki-67 are expressed in GCNIS, lending support to the hypothesis that it arises from a fetal gonocyte (Honecker et al, 2004). Further, the low level of DNA methylation in GCNIS is thought to reflect the stage at which the germ cell became developmentally blocked i.e.…”
Section: Defective Germ Cell Development Seeds Gcnissupporting
confidence: 54%
“…The number of TSPY repeats varies from B23 to 64 among phenotypically normal individual males (Repping et al, 2006), but could change under certain disease conditions (Vijayakumar et al, 2006), suggesting the possibility of genomic instability in this region of the chromosome. TSPY is normally expressed in early gonocytes and prespermatogonia in fetal testis and in spermatogonia, spermatocytes and round spermatids in adult testis (Honecker et al, 2004;Kido and Lau, 2005), and has been postulated to serve normal functions in stem germ cell proliferation and meiotic division (Schnieders et al, 1996;Lau, 1999). TSPY is ectopically expressed in tumor cells in various types of germ cell tumors, including gonadoblastoma, testicular germ cell tumors and male intracranial germ cell tumors, and has been considered as a key marker that is important in the pathogenesis of these types of human tumors Kersemaekers et al, 2005;Hoei-Hansen et al, 2006;Oram et al, 2006;Li et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that certain histologic types express markers associated with distinct maturational stages of germ cell development, which presumably are dependent on a specific gonadal environment. 7,[43][44][45] Lastly, there are some data suggesting that the chromosomal marker characteristic of testicular germ cell tumors, the isochromosome 12p, plays only a minor role in CNS-GCTs. 18,22 As a consequence, it must be debated whether the information generated in the more frequent (and more easily assessable) testicular germ cell tumors can indeed be transferred to CNS-GCTs without scrutiny.…”
Section: Discussionmentioning
confidence: 99%